THE EFFECT OF THE ROLE OF LEADERSHIP ON ORGANIZATIONAL CULTURE AND INTERNAL CONTROL EFFECTIVENESS - Francisca Devi Anita; Dwi Setiawan (AFEBI Accounting Review, 2020)
Good internal control can provide confidence that an organization can achieve its goals with ethical actions. The phenomenon that occurs at this time shows that organizational culture is the main factor causing the emergence of huge scandals that afflict an organization that can prevent the organization from achieving its objectives. Risk in culture occurs when the behavior of members of an organization is not in line with the behavior that the organization wants to instill, causing unethical behavior that can hinder the achievement of goals and influence internal control of the organization.At present, the organizational culture is an essential area within the scope of internal audit work. The role of the current internal auditor is expected to provide adequate assurance regarding one element of risk culture, namely the role of the leader (tone from the top) that has been carried out by following the values and ethics instilled by the organization. Leaders have a significant influence on the formation of culture and internal control systems in organizational units so that the role of internal auditors can provide confidence that the culture formed does not negatively affect overall organizational behavior becomes important.